LEADERSHIP ACCOUNTABILITY AND DEMOCRATIC CONSOLIDATION IN NIGERIAN FOURTH REPUBLIC - OKON, Joshua Akpan (European Journal of Humanities and Educational Advancements, 2023)
Accountability deficits have long plagued democratic endeavours in thirdworld countries, with Nigeria being no exception. This research delves into the ramifications and challenges presented by this lack of accountability within Nigeria’s democratic framework. The absence of accountability not only complicates the democratization process but also poses significant barriers to national advancement. Its repercussions include deterring investments, undermining governance, skewing public policies, fostering financial misappropriations, and engendering corruption. Consequently, Nigeria frequently finds itself unfavourably positioned in corruption perception indices. This lack of accountability is also a leading factor behind rising insecurity, escalating unemployment, pervasive poverty, and disillusionment with democracy. Several challenges underpin this deficit in democratic accountability within Nigeria. The nation grapples with fragile institutions, weakened political parties susceptible to external influences, rampant godfatherism, and overarching leadership issues. For a comprehensive understanding, this study employs a historical approach, critically assessing data from secondary sources. The theoretical framework of accountability is harnessed to shed light on the intricate dynamics of Nigeria’s democratization challenges. To address these concerns, the research offers several recommendations. Emphasis should be placed on data-informed decisionmaking. Efforts should be ramped up in political mobilization and civic education. The appointment of heads of democratic institutions should be independent, and free from presidential influence to ensure impartiality. Furthermore, a robust legal framework is essential, one that is unsparing in its treatment of corrupt public officials, ensuring that malfeasance is consistently penalized